Herbicida glifosato y su impacto negativo en el Ecuador - Velasco Aguiar, Francisco Javier (2024)
Glyphosate is a non-selective, post-emergence, broad-spectrum systemic herbicide used to kill unwanted weeds such as annual and perennial grasses, pastures, and woody plants. In Ecuador, the use of the non-selective systemic herbicide glyphosate is a highly relevant topic; it is a crucial tool for farmers. However, its extensive use has generated an intense debate about its environmental and public health impacts; studies have shown that it can remain active for months. The empirical formula for this substance is C3H8NO5P. Dependence on glyphosate could cause economic problems for Ecuadorian farmers, due to the amount of money they will have to spend on chemical inputs and the possible reduction in the long-term productivity of their crops. Less toxic selective herbicides and regenerative agriculture techniques can also be used to reduce dependence on glyphosate. It is of great importance to have knowledge about sustainable agricultural practices and the good management of chemicals, helping us in making decisions that benefit production levels and care for the environment. Analyzing the impact of glyphosate in Ecuador requires a comprehensive look that considers its environmental, health and socioeconomic effects, as well as current policies and regulations that seek to mitigate its risks. There are methods and technologies to mitigate the unfavorable effects of glyphosate, it is necessary to examine alternative methods and sustainable practices in agriculture. Analyze the impact of the use of the non-selective systemic herbicide glyphosate in Ecuador, glyphosate is a weak organic acid composed of a phosphonomethyl molecule and another glycine.